Perfect gift wrapping ideas 101 ways to personalize your gift using simple, everyday materials - Miyaoka, Hiroe (Tuttle Publishing, 2015)
"Perfect Gift Wrapping Ideas:101 Ways to Personalize Your Gift Using Simple, Everyday Materials turns a time-honored art form into a paper crafter's dream. This is where traditional presentation makes room for whimsy and originality, resulting in a personal touch that becomes part of the gift. From purpose-made paper to wax paper, and from ribbon to a newspaper corsage, you'll be amazed at the array of materials that are already at your fingertips, ready for you to cut, fold, twist, shape and decorate"--Provided by publisher.